Short Communication Staining Effect of Yellow Dye Extracted from Wood of Berberis vulgaris L. on Angiospermic Stem Tissues: Short Communication: Staining Effect of B. vulgaris dye - Bano, Asghari; ullah, Faizan; Dogan, Yunus (Biological Sciences - PJSIR, 2010)
Yellow dye was chemically extracted from wood of Berberis vulgaris L. using water and ethanol and its effectiveness as staining agent for angiosperm stem tissues was studied. The dye stained the lignified tissues of both monocotyledonous as well as dicotyledonous stem cross sections. However, the dye extracted in ethanol (10% w/v) was found more effective to stain the lignified tissues of plants.